Materialism in The Winner Stands Alone and Crazy Rich Asians: Comparative Literature - Devi Panggabean; Siti Norma Nasution; Siamir Marulafau (LingPoet: Journal of Linguistics and Literary Research, 2021)
This study attempts to investigate materialism portrayed in The Winner Stands Alone and Crazy Rich Asians. The author uses novels as the object of research, namely the Crazy Rich Asian novel (2013) by Kevin Kwan and the novel The Winner Stands Alone (2008) by Paulo Coelho. In this work, the author used the sociological theory of literature and the theory of social class to analyze the novel. The method used to write this thesis is a qualitative descriptive method. The results and analyzes found in the novel relate to differences in social class and the differences and similarities of materialism in the two novels. This class difference arises from the existence of social class groups in which they classify their social class, namely the upper class, the middle class and the lower class. he does not want to accept the middle or lower class in his group. The difference in social class is measured in terms of power or wealth, privilege and prestige, which affect the position, lifestyle, habits and behavior of the upper, middle and lower classes. This is why the gap between the three classes is so striking. The conflict that arises is a gap in the social status of a group and in life or family relationships.